Frequency of Regular Voluntary Blood Donors and Factors Associated with Blood Donation in Karachi, Pakistan - Rabisa Batool; Nazish Jaffar; Syeda Ramsha Batool; Insia Hasan; Suresh Klanghani; Suresh Kumar; Rubina Ghani (Pakistan Journal of Medicine and Dentistry, 2020)
Background: